1994
DOI: 10.1103/physrevc.50.2786
|View full text |Cite
|
Sign up to set email alerts
|

Shape changes inKr79

Abstract: High-spin states in Kr were studied using the Cu( O,p3n) reaction at 65 MeV at the Florida State University Tandem-LINAC facility. Prompt p-p coincidences were observed using the Pitt-FSU detector array. Twelve new states were found, along with 19 new transitions. The yrast positive-and negative-parity bands were extended up to spins of (45/2+) and (31/2 ), respectively. Spin assignments were made based on directional correlation of oriented nuclei ratios whenever possible. A cranked-shell-model analysis shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The isotone nucleus 79 Kr (N=43) has the similar oblate ground state deformation and the first neutron crossing is also blocked, therefore it is able to compare to that in 80 Rb. The first band crossing at 0.55 MeV and the second upbend at frequency 0.75 MeV in the negative-parity band in 79 Kr has been attributed to the alignments of a pair of g 9/2 proton and a pair of g 9/2 neutron, which is consistent with that of total Routhian surface calculations in 79 Kr [8] , the latter indicated that the first band crossing occurs at frequency 0.5 MeV due to a pair of g 9/2 proton alignment and the second crossing above 0.6 MeV is attributed to a pair of g 9/2 neutron alignment. The similarities in the crossing frequencies (0.51 and 0.61 MeV of 80 Rb) and the nature of interaction of the quasi-particle bands in 79 Kr and 80 Rb, can suggest that the first and second band crossings in the second negative-parity band of 80 Rb result from the alignments of a πg 9/2 and a νg 9/2 pair, respectively.…”
Section: Experimental Details and Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The isotone nucleus 79 Kr (N=43) has the similar oblate ground state deformation and the first neutron crossing is also blocked, therefore it is able to compare to that in 80 Rb. The first band crossing at 0.55 MeV and the second upbend at frequency 0.75 MeV in the negative-parity band in 79 Kr has been attributed to the alignments of a pair of g 9/2 proton and a pair of g 9/2 neutron, which is consistent with that of total Routhian surface calculations in 79 Kr [8] , the latter indicated that the first band crossing occurs at frequency 0.5 MeV due to a pair of g 9/2 proton alignment and the second crossing above 0.6 MeV is attributed to a pair of g 9/2 neutron alignment. The similarities in the crossing frequencies (0.51 and 0.61 MeV of 80 Rb) and the nature of interaction of the quasi-particle bands in 79 Kr and 80 Rb, can suggest that the first and second band crossings in the second negative-parity band of 80 Rb result from the alignments of a πg 9/2 and a νg 9/2 pair, respectively.…”
Section: Experimental Details and Resultssupporting
confidence: 82%
“…It is difficult for us to define the nature of these band crossings in the absence of experimental information, such as life-time and g-factor measurements as well as relevant theoretical calculations. However, the possible explanation could be presented in comparison to that of its isotone 82 Y as mentioned above, the adjacent nucleus 79 Kr [8] and the first negative-parity band of 80 Rb. Tandel et al [5] and Paul et al [4] have tentatively assigned the configurations π[f 5/2 +p 1/2 ]⊗νg 9/2 or πf 5/2 ⊗νg 9/2 to the second negative-parity band.…”
Section: Experimental Details and Resultsmentioning
confidence: 95%
“…4. Comparison of the νp 1/2 , νf 5/2 , and νg 9/2 bands in isotones 75 Ge, 77 Se [27], and 79 Kr [29]. one interesting feature in Fig.…”
Section: Discussionmentioning
confidence: 86%
“…In the neighboring isotones 77 Se [27] and 79 Kr [28,29], rotational bands built on p 1/2 , f 5/2 , and g 9/2 orbitals have been well established. These bands are compared with those of 75 Ge in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…FIG.3. Kinematic moments of inertia (J(1) ) as a function of rotational frequency for the positive parity and positive signature bands in the N = 44 even-even[13,33,43] isotones (a), N = 44 odd-mass isotones (b), and N = 43 odd-mass[44][45][46] isotones (c).…”
mentioning
confidence: 99%